1998
DOI: 10.1016/s1097-2765(00)80273-7
|View full text |Cite
|
Sign up to set email alerts
|

Key Roles for E2F1 in Signaling p53-Dependent Apoptosis and in Cell Division within Developing Tumors

Abstract: Apoptosis induced by the p53 tumor suppressor can attenuate cancer growth in preclinical animal models. Inactivation of the pRb proteins in mouse brain epithelium by the T121 oncogene induces aberrant proliferation and p53-dependent apoptosis. p53 inactivation causes aggressive tumor growth due to an 85% reduction in apoptosis. Here, we show that E2F1 signals p53-dependent apoptosis since E2F1 deficiency causes an 80% apoptosis reduction. E2F1 acts upstream of p53 since transcriptional activation of p53 target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
146
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(158 citation statements)
references
References 56 publications
10
146
1
1
Order By: Relevance
“…Studies have shown that ARF is not activated by DNA-damaging agents (24), rather by myc, ras, and E2F1 (24,37,38). Unregulated E2F1 activity induces ARF protein expression (37), which in turn stabilizes p53 and thus leads to cell cycle arrest and prevents uncontrolled cell proliferation (39,40). We found increased levels of E2F1 in our NSCLC cells overexpressing CTGF.…”
Section: Discussionmentioning
confidence: 74%
“…Studies have shown that ARF is not activated by DNA-damaging agents (24), rather by myc, ras, and E2F1 (24,37,38). Unregulated E2F1 activity induces ARF protein expression (37), which in turn stabilizes p53 and thus leads to cell cycle arrest and prevents uncontrolled cell proliferation (39,40). We found increased levels of E2F1 in our NSCLC cells overexpressing CTGF.…”
Section: Discussionmentioning
confidence: 74%
“…The concurrent disruption of growth control pathways may have implications in the cell cycle by abrogating the compensatory network that was proposed to exist between p53 and Rb1 pathways. According to this proposed model, loss of functional Rb results in deregulation of the E2F1, which in turn causes stabilization of p53, probably by activating the transcription of ARF (32,(47)(48)(49). Thus, if both pathways are disrupted and p27 is underexpressed, the control of cell proliferation might be profoundly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the E2F1 null background to reduce apoptosis in the lens tissue of Rb null mice demonstrated that previously reported p53-dependent apoptosis seen in the lens tissue of Rb null mice (Morgenbesser et al, 1994) could be due to the deregulated apoptotic function of E2F1 (Tsai et al, 1998) since E2F1 is the upstream regulator of the apoptotic function of p53 (Pan et al, 1998). Together, it is clear that E2F1 may act independently as well as upstream of p53 to induce apoptosis (Pan et al, 1998;Tsai et al, 1998). These ®ndings also suggest that the inhibitory activity of Rb on p53 mediated apoptosis could be mediated through E2F1.…”
Section: Introductionmentioning
confidence: 69%